Information technologies 2011 - Serrano-Cobos, Jorge (Anuario ThinkEPI, 2012)
Review of the developments and trends in computing and telecommunications that have the greatest impact on the documentary and library environment. Among the topics considered are: expanding the markets of large internet companies that want to include new activities, competition between social networks, evolution of ereaders to tablets, increased use of mobile devices (with plenty of features, such as ways to make payments) to the detriment of the PC, tran0sfer of information technology services to the cloud as this provides much more flexibility to institutions, not having so many fixed devices, search engines becoming personal assistants (calendaring, home automation, recommendations), semantic web e-commerce applications, rise of the "open" concept (content, software, data sets), and the professionalization of blogging, which is now more geared to income.
Keywords: Technology trends; Computer; Internet; Mobile devices; Markets; Competition; Consumer information.